Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.4269/ajtmh.2010.09-0433
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Chikungunya Fever, Dakshina Kannada District, South India, 2008

Abstract: The outbreak of chikungunya fever that surfaced in India during late 2005 has affected more than 1.56 million people, spread to more than 17 states/union territories, and is still ongoing. Many of these areas are dengue- and leptospirosis-endemic settings. We carried out a cross-sectional survey in one such chikungunya-affected location in Dakshina Kannada District of Karnataka State to estimate the magnitude of the epidemic and the proportion of chikungunya virus (CHIKV) infections that remained clinically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…All viral detection tests were associated with an immunoassay. We noted that the majority of the studies using IgM ELISA [ 8 , 33 , 35 , 36 , 38 , 44 , 54 , 56 , 60 , 68 , 71 , 76 , 82 , 87 , 108 , 119 , 120 , 120 , 121 , 125 , 128 , 130 133 , 139 – 141 , 143 ], NS1 tests [ 149 ] and/or RT-PCR [ 35 , 60 , 76 , 108 , 118 , 141 , 159 , 160 ] were conducted in an outbreak or post-outbreak context (p<0.001), which is not surprising because these tests are used for detecting acute and/or recent infections. Moreover, nearly all cohort studies that described the incidence and/or seroconversion of arboviral infection also used IgM ELISA and/or RT-PCR methods [ 98 , 103 105 , 107 109 , 111 , 160 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All viral detection tests were associated with an immunoassay. We noted that the majority of the studies using IgM ELISA [ 8 , 33 , 35 , 36 , 38 , 44 , 54 , 56 , 60 , 68 , 71 , 76 , 82 , 87 , 108 , 119 , 120 , 120 , 121 , 125 , 128 , 130 133 , 139 – 141 , 143 ], NS1 tests [ 149 ] and/or RT-PCR [ 35 , 60 , 76 , 108 , 118 , 141 , 159 , 160 ] were conducted in an outbreak or post-outbreak context (p<0.001), which is not surprising because these tests are used for detecting acute and/or recent infections. Moreover, nearly all cohort studies that described the incidence and/or seroconversion of arboviral infection also used IgM ELISA and/or RT-PCR methods [ 98 , 103 105 , 107 109 , 111 , 160 ].…”
Section: Resultsmentioning
confidence: 99%
“…With respect to arboviruses, a wide variation in disease spectrum, including asymptomatic infection, is often observed. In the review, 43 studies reported the proportion of asymptomatic forms; these rates ranged between 22% and 99% for DENV (mean: 67%) [ 23 , 35 , 42 44 , 48 , 51 , 54 , 56 , 59 , 72 , 73 , 76 , 108 , 152 , 163 ], between 4% and 65% for CHIKV (mean: 26%) [ 119 , 120 , 122 , 123 , 125 , 126 , 128 , 129 , 131 , 133 , 141 , 149 , 152 , 163 ] and between 29% and 80% for ZIKV (mean: 55%) [ 8 , 155 , 159 , 160 ]. However, the rates did not differ significantly among continents for either arbovirus, irrespective of whether the highest rates were in the Americas.…”
Section: Resultsmentioning
confidence: 99%
“…The primary goal of such passive surveillance is to monitor epidemiologic trends in diseases. In the case of chikungunya, such monitoring was expected to be delayed due to overwhelming case counts, as had been reported during prior outbreaks in immunologically naive populations [8, 10]. In Puerto Rico, the infrastructure for a passive chikungunya surveillance system (PCSS) was already in place, since the Puerto Rico Department of Health (PRDH) and the CDC had collaboratively operated the passive dengue surveillance system (PDSS) since the 1960s [11].…”
Section: Passive Case Surveillancementioning
confidence: 99%
“…Second, laboratory capacity to routinely test suspected cases did not exist. Third, although severe and potentially fatal manifestations of CHIKV infection [47] had been reported to occur most frequently in infants and the elderly [810], the expected incidence of such manifestations was unclear owing to differences in surveillance methods and potential population-specific differences (eg, underlying comorbidities, demographic age structure, and genetic predisposition). Fourth, multiple acute febrile illnesses (AFIs) are endemic in Puerto Rico, including dengue [11], influenza [12], leptospirosis [13], and melioidosis [14], all of which may be misdiagnosed as chikungunya and vice versa.…”
mentioning
confidence: 99%
“…Indeed intensity of transmission in a population, loosely approximated by the attack rate, could be inversely associated to the proportion of unapparent infection. 21 …”
mentioning
confidence: 99%